PENGEMBANGAN PERSONAL SAFETY SKILL ANAK TUNAGRAHITA DI SLB NUR HUSNINA MELALUI TRAINING ATTENTION, COMPREHENSION AND CREATIVITY - Ahmad Nur Hasyim; Dhea Puspita Cahyaningtyas, Yessa Iriansyah, Dwi Nabila Azahra, Narpati Kolayniskov, Restu Lusiana (Adiba Aisha Amira, 2023)
Education is a conscious effort to bring about the desired changes that can occur in the future. Educational equity and all supporting components should be accessible to every learning group, including children with special needs (ABK), to prevent disparities. In daily life, ABK requires special attention from those around them so that they can maximize their potential. The specificity of ABK can also make them vulnerable to various forms of crime, including sexual violence. This type of crime can be prevented through deep knowledge and understanding of self-defense against potential threats. In this regard, the ability to protect oneself from dangers, know as personal safety skill, is essential. This ability is also based on self-conception or understanding of self-concept for ABK. The method used in this service is mentoring to provide understanding and skills related to sexual violence for intellectually disabled ABK at the SLB Nur Husnina in Madiun City. The results of this service activity include an improvement in personal safety skills, specifically regarding protection against sexual violence.